Místo second look operace v soućasné lécbĕ karcinomu ovaria - Dörr, A; Pilka, L; Jelínek, J; Hortíková, Z (Ceskoslovenska gynekologie, 1993)
The authors evaluate the results of second look operations of ovarian cancer in a group of 34 women. The second look operation was preceded by intraperitoneal and intravenous chemotherapy. This therapeutic protocol contributed to improvement of therapeutic results. In 50% of thus treated women it proved possible to remove the residual tumour and the survival time was prolonged in 75% of women by 1-3 years. The advantages of this therapeutic procedure are according to the authors in particular reduction of the risk of super-radical primary operations and facilitation of the decision whether to terminate treatment or proceed with it.
Keywords: Reoperation; lidé; Female; ženské pohlaví; nádory vaječníků; reoperace; Humans; Ovarian Neoplasms